2014
DOI: 10.1634/theoncologist.2014-0047
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Clinicopathological Features and Prognosis of Emerging Young-Female Breast Cancer in an East Asian Country: A Nationwide Cancer Registry-Based Study

Abstract: Background. A rapid surge of young-female breast cancer (YFBC) has been observed in Taiwan and other East Asian countries. We recently reported that these cases of YFBC, in contrast to their Western counterparts, are predominantly luminal A subtype.YFBC inAsiamayhavedistinctclinicopathologicalfeaturesandoutcomes. Methods. Data collected prospectively by participating hospitals were retrieved from the Taiwan Cancer Database. A total of 15,881 women with newly diagnosed stage I-III breast cancer in 2002-2006 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 30 publications
3
39
0
Order By: Relevance
“…The premenopausal patients accounted for 54.55% of the total breast cancer cases, the proportion was significantly higher than that of postmenopausal patients, and that differed from the corresponding proportion in a Western population 15. This finding suggests the possibility that certain differences in the pathogenesis of breast cancer, considered to be related to ethnicity, age at menarche, marital status, number of pregnancies, number of births, and breastfeeding history 16, 17, 18, 19, may exist between premenopausal and postmenopausal patients.…”
Section: Discussionmentioning
confidence: 93%
“…The premenopausal patients accounted for 54.55% of the total breast cancer cases, the proportion was significantly higher than that of postmenopausal patients, and that differed from the corresponding proportion in a Western population 15. This finding suggests the possibility that certain differences in the pathogenesis of breast cancer, considered to be related to ethnicity, age at menarche, marital status, number of pregnancies, number of births, and breastfeeding history 16, 17, 18, 19, may exist between premenopausal and postmenopausal patients.…”
Section: Discussionmentioning
confidence: 93%
“…In Asia, reports have indicated that the annual incidence of breast cancer has doubled or tripled over the past two decades. In Asia, the onset of breast cancer tends to occur at a younger age and more estrogen receptor (ER) positive or progesterone receptor (PR) positive subtypes, associated with a more favorable clinical-pathological outcome [2]. The etiology of breast cancer has generally been attributed to genetic, reproductive, and hormonal factors.…”
Section: Introductionmentioning
confidence: 99%
“…In Asia, breast cancer incidence is rapidly increasing, and tamoxifen is a principal option of standard adjuvant treatment for ER positive EBC [5,6]. However, the Asian population has been under-represented in international clinical trials on tamoxifen treatment, and thus, the absolute risk of severe complications, such as VTE and uterine cancer, remain uncertain.…”
Section: Introductionmentioning
confidence: 99%